Caesar Hath the Falling Sickness: The Legibility of Early Modern Disability in Shakespearean Drama - Hobgood, Allison P. (Disability Studies Quarterly, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> This essay investigates William Shakespeare’s The Tragedy of Julius Caesar as a disability narrative. In doing so, it reveals that “disabled” was an operational identity category in the early modern period and argues that the play’s treatment of epilepsy illustrates and confounds early modern articulations of disability as wondrous, monstrous, deviant, and pathological. It also suggests that Julius Caesar performs epilepsy as a disability that, in its veritable invisibility, undoes the disciplining of bodily variation these discourses each undertake. In its exploration of epilepsy, Julius Caesar interrogates the idea of early modern disability as a visible, physical phenomenon, instead positing a more complex notion of disability as less overt, decipherable, or legible. Ultimately, this essay introduces disability to Julius Caesar to complicate existing early modern scholarly engagement with difference and presents “Shakespearean” disability studies as a productive critical approach by which to both reanimate dialogue about Renaissance subjectivities and motivate a more politically invested classroom pedagogy. Keywords: disability, Shakespeare, epilepsy, falling sickness, Julius Caesar, visibility, passing, ableism